Comparative Evaluation Of Clinical And Radiographic Horizontal Condylar Guidance Angle Values By Using Two Different Interocclusal Recording Materials In Dentulous Patients (Journal of Pharmaceutical Negative Results, 2022)
Introduction: The success of prosthodontic procedures can be accurately determined by the exact replication of the patient’s condylar path using a semi-adjustable articulator. It allows the clinician to determine the morphology of the occlusal surfaces in relation to the condylar pathway during mandibular movements. If condylar guidance is not exactly registered, it might result in occlusal interferences during movements of the mandible and lengthen chairside adjustment time, which is inconvenient for the patient and dentist.Materials and methods: A total of 20 dentulous patients from 20 to 30 years of age group attending the department of prosthodontics at Sibar institute of dental sciences were selected for the study. Alu wax and jet bite were used to obtain the protrusive interocclusal record (PIR). Protrusive records were then used to program the semi-adjustable articulator to obtain HCGA values on both sides. Using the same protrusive records CBCT radiograph was taken. Radiographic images were traced on tracing paper and HCGA values were measured using Frankfort’s horizontal reference line (the line connecting porion and orbitale) and the mean curvature line (most-superior and most-inferior points of the curvatures) on both sides using a protractor. The data were analyzed by paired sample t-tests and Pearson’s correlation tests.Results: There was no significant difference between the right and left sides in the clinical and radiographic methods using Alu wax PIR. In the clinical method utilizing jet bite PIR, the right side had significantly higher HCGA values than on the left side. On CBCT, no such differences were found.Conclusion: CBCT horizontal condylar guidance angle values were higher than those obtained using the clinical method by using both records. Values obtained from both the methods, i.e., protrusive interocclusal record and cone-beam computed tomography, were compared and correlated.